Analysis of Factors Influencing E-Commerce Adoption in MSMEs in Padang City - Fitraharizki, F; Rahayu, Rita (Jurnal Informatika Ekonomi Bisnis, 2023)
The adoption of e-commerce has become a game-changer for Micro, Small and Medium Enterprises (MSMEs) after the post-pandemic Covid-19 because it has changed consumer behavior and business competition a lot, such as adapting to conditions of environmental characteristics, namely Hygiene, Low-Touch, Less-Crowd, and Low-Mobility. The main objective of this study is to analyze the factors that influence the adoption of e-commerce in MSMEs in Padang City. This study uses the Stage of Model (SoM) research model. The research method uses survey data, primary data types. The sample in this study was 216 from MSME actors in the culinary, fashion, services and hospitality fields in Padang City who had used e-commerce adoption. The data analysis technique used the binomial logistic regression test. Based on data processing, it shows that top management support, company size, employee training and training, Information and Technology (IT) user readiness and relative profits are statistically significant determinants of e-commerce adoption. This study provides direction to MSMEs in Padang City to innovate in business continuity by adopting e-commerce so that their businesses can continue to run amid global economic uncertainty.